Conformational Changes and Catalytic Competency of Hydrolases Adsorbing on Fumed Silica Nanoparticles: II. Secondary Structure - Cruz, Juan C.; Pfromm, Peter H.; Tomich, John M.; Rezac, Mary E. (My University, 2010)
Secondary conformational analysis via Circular Dichroism (CD) and Amide-I FTIR was applied to preparations of Candida antarctica Lipase B (CALB), subtilisin Carlsberg, and the Lipase from Thermomyces lanuginosus (TLL) on fumed silica to confirm that the “hardness” and packing density of the enzymes on the solid fumed silica nanoparticle surface can be used to rationalize the variable enzyme-dependent changes of catalytic competency with surface coverage. “Soft” enzymes should be immobilized at a surface coverage where enzyme-enzyme interactions predominate thereby preventing detrimental structural changes caused by enzyme-support interactions, while “hard” enzymes can be immobilized at low to intermediate surface coverage with good catalytic performance. Multi-layered coverage reduces the superficial average catalytic performance in all cases due to mass transfer limitations.
Keywords: Conformational Stability; Adsorption; Fumed Silica; Protein-surface interactions; FTIR; CD